2017
DOI: 10.1542/peds.2017-0628
|View full text |Cite|
|
Sign up to set email alerts
|

The Primary Care Pediatrician and the Care of Children With Cleft Lip and/or Cleft Palate

Abstract: Orofacial clefts, specifically cleft lip and/or cleft palate (CL/P), are among the most common congenital anomalies. CL/P vary in their location and severity and comprise 3 overarching groups: cleft lip (CL), cleft lip with cleft palate (CLP), and cleft palate alone (CP). CL/P may be associated with one of many syndromes that could further complicate a child's needs. Care of patients with CL/P spans prenatal diagnosis into adulthood. The appropriate timing and order of specific cleft-related care are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 30 publications
0
62
0
24
Order By: Relevance
“…Compared to healthy children, children with CLP are more susceptible to OME [4,5]. Even though the vast majority of patients (approximately 80%) do not have OME at birth [6], statistics have shown that OME occurs at least once before the first birthday in up to 90% of the infants born with CLP [3,7]. Furthermore, as many as 97% of the infants born with CLP suffer concurrent OME within the first two years of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to healthy children, children with CLP are more susceptible to OME [4,5]. Even though the vast majority of patients (approximately 80%) do not have OME at birth [6], statistics have shown that OME occurs at least once before the first birthday in up to 90% of the infants born with CLP [3,7]. Furthermore, as many as 97% of the infants born with CLP suffer concurrent OME within the first two years of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the growth and development of an infant with a cleft palate was lower than the standard [21]. Furthermore, the early feeding of children with cleft palate is correlated with the success of surgery and the patient's prognosis [22]. Therefore, it is very important to master the correct feeding method to maintain the normal growth and development of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals affected by the CLP and their families suffer a great impact in the life quality and psychosocial wellbeing, as this alteration could lead to repercussions on speech, respiration, feed and dental problems. [8][9][10][11] Given the complex context which involves the care for the child with CLP and, specially, the breastfeeding process, it proposes to discuss the maternal transition in the process of breastfeeding child with cleft lip and/or palate, in view of the transition theory.…”
Section: Introductionmentioning
confidence: 99%